OPTIMIZATION OF BUMDES “SEPENUH HATI” IN MANAGING FISHERY POTENTIAL IN LOA DURI ILIR VILLAGE - Dewi Masitah; Gusti Haqiqiansyah; Doni Darmasetiadi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
BUMDes Sepenuh Hati manages several businesses in Loa Duri Ilir Village, which encompass various village potentials in the fisheries sector, including fish farming, fish processing, fishing ponds, and alternative fish feed production. The utilization of these businesses requires the optimization of BUMDes in their management. The purpose of this research is to determine priorities for BUMDes Sepenuh Hati in managing the fishery potential of Loa Duri Ilir Village. The data collection technique used by the researcher involved questionnaires and interviews. The data analysis method uses the Analytic Hierarchy Process (AHP). This method allows for the analysis of the optimization of BUMDes Sepenuh Hati in managing fishery potential based on four aspects: the human resource aspect, the financial aspect, the marketing aspect, and the production aspect. The research results indicate that the main priority criteria for optimizing BUMDes are the human resource aspect, followed by the production aspect, the financial aspect, and lastly the marketing aspect. Based on the analyzed alternatives, BUMDes Sepenuh Hati received a facilitator recommendation from the fish farming group (Pokdakan) to assist in managing the fishery potential of Loa Duri Ilir Village.